Comparison of pregnancy outcome between booked and unbooked mothers at Van Velden Hospital in the Limpopo Province - Madike, Ellen Lopang (My University, 2012)
BACKGROUND: The World Health Organization (WHO) has acknowledged the importance of maternal care and listed it as part of its Millennium Development Goals (MDGs). South Africa has aligned itself with these MDGs. The 5th goal is focused on improving maternal health by reducing the maternal mortality rate by 75% by 2015. There are a number of interventions in place to try and to achieve this goal; the provision of antenatal care is one of these interventions. Antenatal care provides the expectant mother early ongoing monitoring and risk assessment of her pregnancy. It is commonly considered fact that antenatal care improves maternal and perinatal outcomes. In spite of the provision of free maternal health services in South Africa, there are still a significant number of mothers who do not attend antenatal clinics before delivery. No formal study has been done to understand the magnitude of this problem in the Limpopo Province. In view of this, it was decided to conduct this study at the Van Velden Hospital (a rural district hospital in the Mopani District in the Limpopo Province) which has been admitting a significant number of unbooked mothers even after the introduction of free maternal health services in South Africa sixteen years ago. AIM: To compare the pregnancy outcomes (maternal and perinatal) between booked and unbooked mothers who delivered at Van Velden Hospital, a district hospital in the Limpopo Province in South Africa. METHODOLOGY: The setting of this study is the Maternity Unit at the Van Velden Hospital. A cross sectional study design was used. A retrospective record review was done and information for one year (2008/09) will be extracted from the records captured in the District Health Information System. No primary data was collected for this study. RESULTS: This is the first study that looked at broad issues pertaining to the influence of booking status on pregnancy outcomes (maternal and neonatal) at a district hospital in a rural district in the Limpopo Province and probably in South Africa. The study found a prevalence of 15.7% (range: 2.7% to 32.3%) among the study population during the 12 month study period. There were no significant differences in age, marital and employment status of the subjects. However, there were a significant number of teenage pregnancies (13.2%) among the study population, which is of concern. Interestingly, more white women were found not to book in comparison to the black women. There were no significant differences in parity, gravidity and miscarriages between the two groups. Overall, unbooked mothers were more likely to have a preterm baby. This implies antenatal booking can probably prevent preterm deliveries. This study also found unbooked mothers were more likely to have C/S than booked mothers. However, there was no significant difference between booked and unbooked mothers in terms of delivery complications. There was no significant difference between booked and unbooked mothers in terms of birth weight. Although, the babies of unbooked mothers had a significantly lower Apgar score (1 minute) than booked mothers, the difference became insignificant at 10 minutes. There was no maternal mortality during this period. All mothers were discharged home. Overall, perinatal mortality among the study population was 44/ 1000 births. This study found a significant risk of perinatal morbidity (preterm delivery and low Apgar score) among the unbooked mothers. CONCLUSION: This research was undertaken to develop a model that could be used by both the provincial and national governments to evaluate the prevalence and impact of booking status of pregnant women in rural district hospitals in South Africa.
Keywords: Hospital Administration; Delivery Room